The Etiology of Neuromuscular Hip Dysplasia and Implications for Management: A Narrative Review - Ana Presedo; Erich Rutz; Jason J. Howard; Michael Wade Shrader; Freeman Miller (MDPI AG, 2024)
This study summarizes the current knowledge of the etiology of hip dysplasia in children with neuromuscular disease and the implications for management. This article is based on a review of development of the hip joint from embryology through childhood growth. This knowledge is then applied to selective case reviews to show how the understanding of these developmental principles can be used to plan specific treatments. The development of the hip joint is controlled by genetic shape determination, but the final adult shape is heavily dependent on the mechanical environment experienced by the hip joint during growth and development. Children with neuromuscular conditions show a high incidence of coxa valga, hip dysplasia, and subluxation. The etiology of hip pathology is influenced by factors including functional status, muscular tone, motor control, child's age, and muscle strength. These factors in combination influence the development of high neck-shaft angle and acetabular dysplasia in many children. The hip joint reaction force (HJRF) direction and magnitude determine the location of the femoral head in the acetabulum, the acetabular development, and the shape of the femoral neck. The full range of motion is required to develop a round femoral head. Persistent abnormal direction and/or magnitude of HJRF related to the muscular tone can lead to a deformed femoral head and a dysplastic acetabulum. Predominating thigh position is the primary cause defining the direction of the HJRF, leading to subluxation in nonambulatory children. The magnitude and direction of the HJRF determine the acetabular shape. The age of the child when these pathomechanics occur acts as a factor increasing the risk of hip subluxation. Understanding the risk factors leading to hip pathology can help to define principles for the management of neurologic hip impairment. The type of neurologic impairment as defined by functional severity assessed by Gross Motor Function Classification System and muscle tone can help to predict the risk of hip joint deformity. A good understanding of the biomechanical mechanisms can be valuable for treatment planning.